Looking Again. Issue 1 (1st August 2019) - Maier, Danica
Enacting the subject of ornamentation through unfolding a deteriorating repetition within its reading, this paper is presented as a performative text. Illuminating rather than telling, key focus within the paper draws on: detail and curiosity as necessities during both the making process and audiences viewing of ornamentation; the hidden and overlooked seen in domestic pattern and the rich potential for subversion; the whole versus the single, how looking and making can be akin to fractals; the un-repeating repeat or difference of the same as seen through visual rhythm disrupted by the glitch; how repetition of text transforms it into the decorative; transformation through repetition connected to the joys of labour and its associate cousins of repeated action, making, boredom, rhythm, muscle memory, sex.